Keteladanan Sebagai Metode Pendidikan Karakter - Munawwaroh, Azizah (Jurnal Penelitian Pendidikan Islam, 2019)
Education includes character education, which is a deliberate process to instill character in students. Character education is very important, because with character, humans will be noble and become special beings compared to other creatures and even fellow human beings. Because of the very importance of character education, the existence of a method to achieve it also becomes very important. This study aims to elaborate exemplary methods in character development. By using library research and reflection methods, this research found that modeling is the most important and most effective character education method provided that: it is comprehensively carried out by educators in each educational environment; conducted together with other educational methods; and shown in three aspects: cognitive, affective, and psychomotor.